The Influence of Price and Product Quality on Consumer Satisfaction at Pagar Dewa Fishing Shop - Subandrio Subandrio; Feggy Fernandes (Penerbit Jurnal Indonesia, 2022)
This study aims to determine the effect of price and product quality on consumer satisfaction at the Pagar Dewa fishing shop. This type of research uses descriptive quantitative research methods. The population used in this study were customers of the Pagar Dewa fishing shop. The number of respondents in this study were 75 people. Methods of data collection using questionnaires and using analytical techniques using multiple linear regression analysis test and hypothesis testing, namely t test and f test. Based on the results of multiple linear regression obtained the form of the regression equation Y = 2.321 + 0.379 (X₁) + 0.251 (X₂) and the results of the t test and f test of this study can be concluded that price has a significant effect on consumer satisfaction, this is evidenced by the results of the t test showing the value of t_hit >t_table (3,318 > 2.002) and (sig = 0.03 < 0.050). This means that H_0 is rejected and H_a is accepted. Product quality has a significant effect on consumer satisfaction, this is evidenced by the results of the t test showing the value of t_hit> t_table (3.232> 2.002) and (sig = 0.02 < 0.050). This means that H_0 is rejected and H_a is accepted. price (X₁) and produk quality (X₂) together have a significant effect on consumer satisfaction (Y) at Pagar Dewa Fishing Shop, this is evidenced by the F test showing the value of F_count>F_table, namely (50.277 > 3.16) and (sig. = 0.00 < 0.050). This means that H_0 is rejected and H_a is accepted.